Improvement of Post-Nickel Mining Soil Quality for Plant Revegetation Growth Media through Utilization of Humic materials and Compost PENINGKATAN KUALITAS TANAH BEKAS TAMBANG NIKEL UNTUK MEDIA PERTUMBUHAN TANAMAN REVEGETASI MELALUI PEMANFAATAN BAHAN HUMAT - Ikbal .; Iskandar .; Sri Wilarso Budi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
The purpose of this study was to analyze the effect of humic materials and compost on chemical properties and growth of revegetation plant. The research was conducted at the greenhouse of PT Antam (Persero) Tbk., District Pomalaa, Southeast Sulawesi. Soil analysis was carried out at the Laboratory of Soil Research of Bogor Agricultural University. The experiment was used a completely randomized factorial design with two factors; Humic materials dose (0.00; 0.5; and 1.0 ml / polybag) and compost dose (0.0; 1.0; and 2.5 kg/polybag). Plant indicator that used in this experiment was sengon (Paraserianthes falcataria). The result showed humic materials and compost improved the chemical properties of growth media than control. Treatment with the provision of humic materials only did not fully improved soil chemical properties, while treatments of compost and combination of humic materials and compost able to increase organic C, N-total, CEC, and cations alkaline soil (Ca-dd, Mg-dd, K-dd, and Na -dd). On the plant growth showed that the humic materials and compost gave significant effect on plant height, root length and biomass. Treatment between humic materials and compost had result significant in root length and biomass. The best treatment at the greenhouse was reached by 0.5 ml humic materials and compost 2.5 kg.Key words: chemical property, plant height, root lenght, biomass